Kesenian Rampak Buto Sebagai Sumber Penciptaan Tari Gedroex Wanodya Oleh Krincing Manis Dance Studio, Sleman, Yogyakarta - Luvita Pradana Puspita Sari; Umilia Rokhani (Institut Seni Indonesia Yogyakarta, 2024)
Traditional folk art is a traditional art that lives and develops in communities outside the Yogyakarta’s Palace. The form of development presented creates creativity from the supporting community, one of them is the Rampak Buto Art, which is one of the creativity in the Jatilan performing arts. Rampak Buto Art exists as a creativity in the local community which is dominated by men, seen from the performances and the various clothing attributes they use.One of creativity in the Rampak Buto performance is the creation of the Gedroex Wanodya dance. This dance was created by the Krincing Manis Dance Group, this group is existence as the only one Rampak Buto group dominated by female dancers in Yogyakarta. The Gedroex Wanodya’s dance was created by contemporary choreography so that it becomes a new form of Rampak Buto Art.This research using qualitative methods and an approach using Choreographic Analysis. In the choreography’s process, the researcher acted as a participant observer, that she went directly to the research object by acting as director of the Gedroex Wanodya’s dance work.